Pandangan Hukum Islam Terhadap Mekanisme Pemanfaatan Tanah Wakaf Masjid Amal Muslimin (Studi Kasus di Kelurahan Medan Tenggara, Kecamatan Medan Denai, Kota Medan) - Raiehan Baihaqi; Syafruddin Syam (LPPM Universitas Ekasakti Padang, 2023)
The presence of waqf land certainly provides many benefits for the community's survival. However, in practice, most waqf land is still used individually or privately by the community. One of them happens to the waqf land located at the Amal Muslimin Mosque in Southeast Medan Village, Medan Denai District, Medan City, where this land is eventually used by local residents for personal interests, they build houses for their residences, until now, which in its utilization, it violates the basic substance of the waqf practice in accordance with Islamic teachings. Land that is waqfed can only be utilized for collective welfare, not personal. So this research aims (1) to find out the law of utilizing waqf land belonging to the Muslim Amal Mosque according to the views of Islamic Law; and (2) The law of utilizing waqf property for individual private interests. To achieve the above objectives, this research uses a normative-empirical method, using references from various books, journals, legislation, observation and interview results, as well as other supporting literacy. The results of this study reveal that using the waqf land of the Amal Muslimin Mosque for personal gain by building houses for local residents to live in is prohibited in the positive law study law and prohibited in Islamic sharia.